2021
DOI: 10.1088/1741-4326/ac359d
|View full text |Cite
|
Sign up to set email alerts
|

Study of ion cyclotron range of frequencies heating characteristics in deuterium plasma in the Large Helical Device

Abstract: The characteristics of ion cyclotron range of frequencies (ICRF) minority ion heating with a hydrogen minority and deuterium majority plasma were studied by ICRF modulation injection experiments in the Large Helical Device (LHD). In recent experiments with deuterium plasma, no significant increase in the neutron emission rate due to ICRF second harmonic deuteron heating was observed. Therefore, in this study, the neutron emission rate was used to refer to the information regarding the thermal ion component. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…In a low hydrogen ratio below 10% for deuterium plasmas, the minority ion ratio did not always seem to agree between the measurement and the prediction from wave heating results. We could not get apparent peak heating efficiency below the minority ion ratio of 10% from the actual plasma experiments, but the dependence for heating efficiency was consistent with the prediction from wave absorption for the ion ratio exceeding 10% [7]. This is one of the long-standing mysteries of ICRF heating in the LHD.…”
Section: Introductionsupporting
confidence: 48%
See 2 more Smart Citations
“…In a low hydrogen ratio below 10% for deuterium plasmas, the minority ion ratio did not always seem to agree between the measurement and the prediction from wave heating results. We could not get apparent peak heating efficiency below the minority ion ratio of 10% from the actual plasma experiments, but the dependence for heating efficiency was consistent with the prediction from wave absorption for the ion ratio exceeding 10% [7]. This is one of the long-standing mysteries of ICRF heating in the LHD.…”
Section: Introductionsupporting
confidence: 48%
“…However, the hot plasma dielectric tensor for the integral formula for the LEAF is insufficient for the wave absorption component because the harmonics cyclotron damping is relatively strong compared to electron Landau damping for wave absorption using the ICRF heating in the mixed plasma. Since it is reported that the plasma heating efficiency evaluated from diamagnetic energy with the amplitude modulation of ICRF power agrees with the wave absorption using a Fourier-transformed hot plasma dispersion relation with a single toroidal mode on the poloidal cross-section [7], we used a hot plasma tensor ϵ hot, stix k 0 with a single parallel wavenumber as a substitute for the hot plasma tensor ϵ hot, stix in the FEM calculations.…”
Section: A Simple Wave Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma ray diagnostics during a neutral-beam-heated deuterium plasma discharge is regarded as a less important diagnostics compared with integrated neutron diagnostic [25], which can directly provide a beam ion confinement property [26][27][28] because neutrons are mainly produced by socalled beam-thermal reactions in LHD deuterium plasma experiments [29]. Recently, an ion cyclotron resonance frequency (ICRF) wave-heated deuterium plasma experiment was performed with relatively low-power ICRFheated deuterium plasma [30]. Gamma ray spectroscopy can provide the energy distribution of MeV range ICRF tail ions in a deuterium plasma experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The classical confinement of energetic ions [20][21][22][23] as well as energetic ion transport due to magnetohydrodynamics [24][25][26][27][28][29] have been studied using comprehensive neutron diagnostics [30][31][32][33][34][35][36][37][38]. The installation of gamma ray systems was planned [39] to understand the MeV ion confinement created by the ion cyclotron range of frequency wave heating experiments [40]. Additionally, gamma ray diagnostics played an important role in knock-on tail observation [41][42][43] through the 6 Li(d, p ′ 𝛾) 8 Be reaction [44,45] and a study toward aneutronic p-11 B fusion [46].…”
Section: Introductionmentioning
confidence: 99%